The dirt riddles : poems - Walsh, Michael, 1973- (University of Arkansas Press poetry series., 2010)
Michael Walsh is the author of a chapbook, Adam Walking the Garden. He is a recipient of a Minnesota State Arts Board Fellowship and a residency at the Anderson Center for Interdisciplinary Studies. A graduate of Knox College and the University of Minnesota (MFA), he works as a course coordinator in the English Department at the University of Minnesota and lives in Minneapolis, Minnesota. This is his first book.